Selection and characterisation of Red Geysers in the MaNGA survey. Issue Volume 15:Issue S359(2020) (March 2019) - Ilha, Gabriele S.; Riffel, Rogemar; Rembold, Sandro B.; Schimóia, Jáderson S.
Abstract: Red Geysers are quiescent galaxies that show a bi-polar outflow, but the mechanism that produces this outflow is still unclear. Using MaNGA data, we find that Red Geysers correspond to ∼1.6% of the sample of galaxies already observed by MaNGA. About ∼16% of the Red Geysers show clear evidence of Active Galactic Nuclei, as revealed by emission-line ratios.